Implicit content of the Ukrainians’ attitudes towards the war in Donbas - Васютинський, В. О. (Київський національний університет імені Тараса Шевченка, 2017)
The article is devoted to the coverage of the empirical study results on the Ukrainians’ attitudes towards the war in Donbas. These attitudes are regarded as a psychological phenomenon that is in the state of active formation. Using half-standardized interviews, 150 residents of three cities in different regions of Ukraine were interviewed. Their subjective stories about their lives have been analyzed. Only 17.3 % of respondents mentioned the war in one way or another. The differences between the representatives of these two groups – those who mentioned the war and those who did not mention it – were fixed. As a result of the comparison, it has been established that the implicit content of the respondents’ attitudes towards the war appeared in the form of latent, background, and indistinct concepts that cumulatively determined the emotional and semantic content of the corresponding positions. Attitudes towards the war were not at the center of the actual experiences and values of the interviewed people. It was also inferior to the subjective significance of the financial disadvantages. The interests of the individuals who actively determined their attitudes towards the war, were clearly directed at the social content of individual and collective life, the material difficulties of the environment, the majority’s inability to the desired psychological transformations, and the critical attitudes towards the authorities. These features affected the general state of wartime mass consciousness, but can become the leading trends in its development in the event of fundamental changes in the social and political situation in the country.

За допомогою напівстандартизованого інтерв’ю 150 респондентів у трьох регіонах України визначено імпліцитний зміст їхніх ставлень до війни на Донбасі. Такі ставлення мають вигляд фонових концептів, що не перебувають у центрі свідомості та істотно поступаються перед переживанням матеріальних негараздів. Вони спрямовані на соціальний зміст індивідуальної і колективної життєдіяльності, матеріальні труднощі оточення, неспроможність більшості до бажаних психологічних трансформацій, критичне ставлення до влади.
Імпліцитний зміст ставлення українців до війни на Донбасі
Keywords: implicit content of attitudes; background concepts; attitudes toward war; individual and collective life activities; political and ideological self-determination; імпліцитний зміст ставлень; фонові концепти; ставлення до війни; індивідуальна і колективна життєдіяльність; політико-ідеологічне самовизначення